Clinicopathological and prognostic significance of CDH1 hypermethylation in hepatocellular carcinoma: a meta-analysis - Wu, Xiaoyu (Cancer Manag Res, 2019)
BACKGROUND: The patients with hepatocellular carcinoma (HCC) have poor prognosis due to being diagnosed at late stage or recurrence following surgery. It’s critical to identify effective biomarkers that can improve overall diagnosis and treatment of HCC. METHODS: We performed a meta-analysis of all relative studies reporting the clinicopathological significance of CDH1 hypermethylation in HCC by using Review Manager 5.2. A comprehensive literature search was performed in EMBASE, PubMed, Web of Science and Google Scholar databases. Kaplan Meier Plotter online database was used for the determination of correlation between CDH1 mRNA expression and overall survival in patients with HCC. Odds Ratios (OR) with 95% corresponding confidence intervals (CIs) were calculated. A total of 12 relevant studies were included in the meta-analysis with 981 patients. RESULTS: The positive rate of CDH1 hypermethylation was significantly higher in HCC than in normal liver tissue; and the pooled OR was 4.34 with 95% CI 2.50–7.56, P<0.00001. CDH1 promoter in HCC was more frequently hypermethylated compared to the group of chronic liver disease (CLD); OR was 4.83 with 95% CI 2.67–8.72, P<0.00001. However, the rate of CDH1 promoter hypermethylation was not correlated with different grades as well as stages. High CDH1 mRNA expression was significantly correlated to better overall survival in all 231 HCC patients compared to 133 HCC patients with low level CDH1 mRNA expression; HR was 0.6 with 95% CI 0.42–0.85, P=0.0034. CONCLUSION: In summary, CDH1 promoter hypermethylation is a risk factor and promising biomarker for HCC carcinogenesis and diagnosis, as well as a predictor of poor prognosis.